2021
DOI: 10.1002/etc.5187
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Life‐History Traits of Hypogastrura viatica (Collembola) Exposed to Imidacloprid Through Soil or Diet

Abstract: Collembola (springtails) are important members of soil communities worldwide by contributing to degradation of organic matter. In nature, Collembola might be exposed to the neonicotinoid insecticide imidacloprid, which is fairly persistent in soil. We exposed the widespread Hypogastrura viatica to imidacloprid through soil or food, and monitored the animals during exposure and a post-exposure period. We recorded effects on life-history traits affecting individual fitness; that is, mortality, behavioral activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…We found that different soil environmental variables were correlated with each genus of soil Collembolans in numerous ways, and this confirmed our hypothesis that responses to land degradation would differ across the soil Collembolan taxa (H2). Previous studies revealed that life histories, feeding guilds, propagation characteristics and adaptability mechanisms differed dramatically across soil Collembolan taxa [ 40 , 41 , 42 ]. Consequently, in this study, a variety of responses to land degradation were observed across the different genera of soil Collembolans.…”
Section: Discussionmentioning
confidence: 99%
“…We found that different soil environmental variables were correlated with each genus of soil Collembolans in numerous ways, and this confirmed our hypothesis that responses to land degradation would differ across the soil Collembolan taxa (H2). Previous studies revealed that life histories, feeding guilds, propagation characteristics and adaptability mechanisms differed dramatically across soil Collembolan taxa [ 40 , 41 , 42 ]. Consequently, in this study, a variety of responses to land degradation were observed across the different genera of soil Collembolans.…”
Section: Discussionmentioning
confidence: 99%
“…Then T (t) : X → X is a C 0 semigroup generated by the operator A defined on D(A). Define F : X → X by (9) for x ∈ Ω and φ ∈ X . Then (7) can be rewritten into the following abstract differential equation…”
Section: Basic Properties With the Natural Phase Spacementioning
confidence: 99%
“…Following are typical motivative scenarios to incorporate spatially varying feedback delays in a model system. The first example is the development of Collembola, with its egg development and hatching being affected by environmental pollution, such as copper lead, zinc [ 31 ] and other toxic substances [ 9 ]. However, these toxic substances are not evenly distributed in soil [ 9 ], which induces a non-uniform development time in the spatial scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field concentrations of imidacloprid (Silva et al 2019 ) can cause negative effects for non-target, soil-living arthropods (de Lima e Silva. et al 2017 ; van Gestel et al 2017 ; Kristiansen et al 2021 ). One such group is the Collembola (springtails), which are important members of the soil fauna (Rusek 1998 ), and among the soil animals that are most sensitive to pesticides originating from agriculture (Joimel et al 2022 ), such as neonicotinoids.…”
Section: Introductionmentioning
confidence: 99%